A Historical Survey of Southern African Liturgy: Liturgical Revision from 1908 to 2010 - Bethke, Andrew-John (Journal of Anglican studies, 2017)
The article surveys liturgical developments in the Anglican Church of Southern Africa from 1908 to 2010. The author uses numerous source documents from several Anglican archives to analyse the experimental and fully authorized liturgies, detailing the theological and sociological shifts which underpinned any significant changes. The author includes several sources which, until this point, have not been considered; particularly in relation to the reception of newer liturgies. These include letters, interviews and newspaper articles. Influences from the Roman Catholic Church, the Church of South India, the Church of England, the Episcopal Church in the USA and the Church of New Zealand all contributed to the authorized rites in the local church. Furthermore, the article shows that local, traditionally disenfranchised voices are now beginning to be included with liturgical transformation.